Pollinators of cucurbit crops: Diversity, efficiency and conservation challenges - Ikram, M; Srinivasan, M R; Suganthi, A; Saminathan, V R; Auxcilia, J; Jayakanthan, M; Bimal, Kumar Sahoo; Ramya, A R; Deva, Dharshini V; Iqra, Ali (Plant Science Today, 2025)
Pollination is critical to crop productivity, with about 87 % of global food crops relying on pollinators. Cucurbits (Cucurbitaceae), including cucumber, pumpkin, melon, bitter gourd and squash, are highly dependent on insect pollination because of their monoecious or andromonoecious flowering systems. Effective fruit set and quality in these crops are linked to floral biology, stigma receptivity and synchronisation with pollinator activity. Pollination efficiency varies among cucurbit species and pollinators. In cucumber (Cucumis sativus), Apis mellifera accounted for 96.5 % of floral visits during the short rainy season and 64.3 % during the long rainy season, producing the highest fruit weight (1184.5 g) and seed number (472.8 seeds/fruit). In muskmelon (Cucumis melo), Apis florea and Apis cerana contributed to 93.3 % and 83.3 % fruit set, respectively, highlighting the role of native bees in successful fertilisation. In watermelon (Citrullus lanatus), at least six bee visits per pistillate flower are needed for full fruit development, with Bombus impatiens exhibiting greater pollen deposition efficiency than honey bees. Native squash bees (Peponapis and Xenoglossa spp.) are the most effective pollinators of pumpkin and squash due to early morning foraging and floral specialisation. Pollinator activity is influenced by temperature, humidity, pesticide use and habitat conditions. Declines in pollinator populations from habitat loss, agrochemicals and climate change pose serious risks to cucurbit yields. Conserving pollinator diversity and adopting pollinator-friendly farming practices are essential for sustaining productivity and ensuring the ecological resilience of cucurbit production systems.